Development Of Municipal Solid Waste Generation And Recyclable Components Rate Of Kuala Lumpur: Perspective Study. - Saeed, Mohamed Osman; Hassan, Mohd Nasir; Abdul Mujeebu, M. (2008)
This paper presents a forecasting study of municipal solid waste generation (MSWG) rate and potential of its recyclable components in Kuala Lumpur, the capital city of Malaysia. The generation rates and composition of solid wastes of various classes such as street cleansing, landscape & garden, industrial & constructional, institutional, residential and commercial are analyzed.